1982
DOI: 10.1128/aac.21.2.224
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of fosmidomycin, a new phosphonic acid antibiotic

Abstract: The pharmacokinetics offosmidomycin was investigated in animals and humans after parenteral and oral dosing. In dogs the serum concentration was 54.8 ,ug/ml at 0.25 h after an intravenous dose of 20 mg/kg, and the half-life was 1.14 h. Peak concentration was 41.4 ;ig/ml after an intramuscular dose of 20 mg/kg and 16.6 ,g/ ml after an oral dose of 40 mg/kg. In volunteers, the serum concentration 0.25 h after dosing was 157 jig/ml after an intravenous dose of 30 mg/kg, 12.3 ,ug/ml after an intramuscular dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 9 publications
1
45
0
Order By: Relevance
“…Abou-El-Makarem and his colleagues examined this possibility by tying up the renal pedicles in rats, so that clearance by the kidney was prevented, and the results indicated that when clearance by the kidney is prevented, biliary excretion increased by 10% (12). Fosmidomycin has a short half-life of 1.7 h and is rapidly cleared by the kidneys (43). It is a small molecular weight polar agent which may not be cleared in high quantities through bile according to the molecular weight threshold hypothesis.…”
Section: Analysis Of the Outliersmentioning
confidence: 99%
“…Abou-El-Makarem and his colleagues examined this possibility by tying up the renal pedicles in rats, so that clearance by the kidney was prevented, and the results indicated that when clearance by the kidney is prevented, biliary excretion increased by 10% (12). Fosmidomycin has a short half-life of 1.7 h and is rapidly cleared by the kidneys (43). It is a small molecular weight polar agent which may not be cleared in high quantities through bile according to the molecular weight threshold hypothesis.…”
Section: Analysis Of the Outliersmentioning
confidence: 99%
“…[5,8] Various research groups are involved in the design of novel DXR inhibitors. [3] Molecular field analyses, as well as crystallographic studies, could already contribute in defining structural requirements for the development of potent DXR inhibitors.…”
mentioning
confidence: 99%
“…Clinical studies with a combination of fosmidomycin and clindamycin, which was shown to act synergistically, are currently ongoing [7][8][9]. In previous pharmacokinetic studies, a microbiological assay with Enterobacter cloacae as test organism was used for the determination of fosmidomycin in biological fluids [10]. For the current studies, a more convenient and reliable assay is required in order to monitor the efficiency of the dose regimen and to optimize the therapy.…”
Section: Introductionmentioning
confidence: 96%